Transcriptional Regulation of Fucosyltransferase 1 Gene Expression in Colon Cancer Cells - Fumiko Taniuchi; Koji Higai; Tomomi Tanaka; Yutaro Azuma; Kojiro Matsumoto (The Scientific World Journal)
The α1,2-fucosyltransferase I (FUT1) enzyme is important for the biosynthesis of H antigens, Lewis B, and Lewis Y. In this study, we clarified the transcriptional regulation of FUT1 in the DLD-1 colon cancer cell line, which has high expression of Lewis B and Lewis Y antigens, expresses the FUT1 gene, and shows α1,2-fucosyltransferase (FUT) activity. 5′-rapid amplification of cDNA ends revealed a FUT1 transcriptional start site −10 nucleotides upstream of the site registered at NM_000148 in the DataBase of Human Transcription Start Sites (DBTSS). Using the dual luciferase assay, FUT1 gene expression was shown to be regulated at the region −91 to −81 nt to the transcriptional start site, which contains the Elk-1 binding site. Site-directed mutagenesis of this region revealed the Elk-1 binding site to be essential for FUT1 transcription. Furthermore, transfection of the dominant negative Elk-1 gene, and the chromatin immunoprecipitation (CHIp) assay, supported Elk-1-dependent transcriptional regulation of FUT1 gene expression in DLD-1 cells. These results suggest that a defined region in the 5′-flanking region of FUT1 is critical for FUT1 transcription and that constitutive gene expression of FUT1 is regulated by Elk-1 in DLD-1 cells.